The Optimization of Aerobic Bacteria Inactivation in Tilapia (Oreochromis niloticus) Fillets using Micro-Nano Bubbles of Carbon Dioxide and Shelf-Life Extension - Naewkanya, Pattama; Petiraksakul, Anurak (Applied Science and Engineering Progress, 2025)
This study aims to examine the influence of NaOCl, NaCl and contact time on the inactivation of aerobic bacteria in tilapia fillets treated with micro-nano bubbles of CO2 (CO2 MNB) in a washing process of fish fillets, and compared to soaking with tap water and untreated fillets for their shelf-life extensions. Response surface methodology (RSM) with a central composite design was used to compare and predict of the inactivation effects. The fish fillets were soaked in a NaOCl solution before washing with a NaCl solution and CO2 MNB produced from an MNB generator system, maintaining the liquid temperature in the range of 4–7 °C for all experiments. According to the regression analysis from the experimental design, aerobic bacteria inactivation was reduced by 1.509 log CFU/g at 100 mg/L NaOCl, 10%w/v NaCl, and a contact time of 32 min with CO2 MNB. The experimental value of the reduction of aerobic bacteria by 1.503 ± 0.009 log CFU/g (before washing 5.623 log CFU/g; after washing 4.120 log CFU/g) was found after treatment under the aforementioned condition. The number of aerobic bacteria counted on the tilapia fillets treated with the upper condition after being stored at 4 ± 2 °C for 7 d was below the acceptable limits, but untreated and treated with tap water had bacteria counts exceeding the upper microbial limit (6 log CFU/g). The combined results showed that the NaOCl, NaCl solution and CO2 MNB treatment could extend the storage time by more than 7 d.